(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article focuses on the historical regularity of public buildings and structures, the concept and content of office centers, coworking centers, their dependence on the socio-political structure of States, the growth of business, the perfection of the legislative framework, economic growth and population growth of large cities. The article deals with the history of urban planning formation of functional and planning infrastructure of urban spaces in the context of financial and economic development of public areas, from the position of typological classification of modern office and business centers.